Use of home pulse oximetry with daily short message service messages for monitoring outpatients with COVID-19: The patient's experience. (December 2021) - Vaughan, Laura; Eggert, Lauren E; Jonas, Andrea; Sung, Arthur; Singer, Sara
Studies have shown COVID-19 patients may have a low oxygen saturation (SpO2 ) independent of visible respiratory distress, a phenomenon termed "silent hypoxia." Silent hypoxia creates uncertainty in the outpatient setting for clinicians and patients alike. In this study, we examined the potential for pulse oximeters in identifying early signs of clinical deterioration. We report descriptive results on COVID-positive patients' experiences with a comprehensive home monitoring tool comprised of home SpO2 measurements with a novel symptom-tracking short message service/text messaging application. Of patients who required hospitalization, 83% sought care as a result of low pulse oximeter readings. Nearly all patients who did not require hospitalization reported that having a pulse oximeter provided them with the confidence to stay at home. Essentially all patients found a home pulse oximeter useful. Keeping COVID-19-positive patients at home reduces the potential for disease spread and prevents unnecessary costs and strain on the healthcare system.